Psychiatric Co-morbidities and Body Shape Dissatisfaction in Adolescents with Obesity – A School Based Case Controlled Study - S, Arumuganathan; Sagar, Rajesh; Mehta, Manju; T, Siva Ilango (Indian journal of pediatrics, 2021)
Objective To compare the psychiatric co-morbidity and Body image disturbances of obese adolescents with age and gender matched normal weight controls. Methods A case control study was conducted in a school in New Delhi. Nine hundred seventy six students were screened for height and weight and body mass index (BMI) was calculated. Thirty one consenting obese students as per International Obesity Task Force (IOTF) guidelines and 31 age and gender matched normal weight students were recruited for the study. Semi-structured questionnaires were used to assess socio-demographic details, psychiatric co-morbidity using the Mini International Neuropsychiatric Interview- child and adolescent version (MINI-KID), and body image disturbances by Body Shape Questionnaire - the 8 items shorter version (BSQ-8C). The authors examined the relationships between variables measured on these scales and anthropometric data. Results Of the 976 students screened, 33 (3.38%) students were obese; 21 boys (3.25%) and 12 girls (3.65%). Of the 31 consenting obese subjects and an equal number of age and sex matched controls included in the study, 68% and 7% of them were diagnosed with a DSM-IV disorder based on MINI-KID respectively. The most common diagnosis in the obese group was social phobia (36%) followed by specific phobia (19%) and major depressive disorder (19%). Ninety percent of the obese samples expressed concern over body shape as against 29% in the control subjects. Among obese subjects, 36% expressed mild concern, another 36% expressed moderate concern and 19% expressed marked concern over body shape. Conclusions Psychiatric co-morbidity and body shape dissatisfaction are common in obese non-treatment seeking adolescents and warrants need for comprehensive evaluation and management of these issues to manage the epidemic of adolescent obesity in India.